2021
DOI: 10.3390/ijms22094382
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Clinical Role of Spermine in Prostate Cancer

Abstract: Spermine, a member of polyamines, exists in all organisms and is essential for normal cell growth and function. It is highly expressed in the prostate compared with other organs and is detectable in urine, tissue, expressed prostatic secretions, and erythrocyte. A significant reduction of spermine level was observed in prostate cancer (PCa) tissue compared with benign prostate tissue, and the level of urinary spermine was also significantly lower in men with PCa. Decreased spermine level may be used as an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 104 publications
(127 reference statements)
3
8
0
Order By: Relevance
“…Furthermore, the authors observed relevant associations between reduced putrescine levels and upregulation of spermidine synthase (SRM), as well as lower spermine and increased spermidine/spermine N1-acetyltransferase 1 (SAT1) and spermine oxidase (SMOX) expression. In agreement with these results, other authors also reported a reduction in spermine and putrescine levels [34,58,74,75], as well as an overexpression of enzymes involved in the polyamine pathway [83][84][85].…”
Section: Benign Tissue Vs Pca Tumorsupporting
confidence: 76%
“…Furthermore, the authors observed relevant associations between reduced putrescine levels and upregulation of spermidine synthase (SRM), as well as lower spermine and increased spermidine/spermine N1-acetyltransferase 1 (SAT1) and spermine oxidase (SMOX) expression. In agreement with these results, other authors also reported a reduction in spermine and putrescine levels [34,58,74,75], as well as an overexpression of enzymes involved in the polyamine pathway [83][84][85].…”
Section: Benign Tissue Vs Pca Tumorsupporting
confidence: 76%
“…Surprisingly, subjects with both radiographic and biochemical recurrence expressed a marginally significant increase of SAT1/2 level in prostate tissue than those without recurrence [34]. Though the change in SAT1/2 levels could compromise different cellular responses, for instance polyamine oxidation [34,35], it served as potential mechanism for the decrease in spermine concentrations in body fluids and tissues, as well as a diagnostic biomarker for prostate cancer [36].…”
Section: Urological Cancersmentioning
confidence: 99%
“…An elevated urine spermidine level was found in PCa compared with noncancerous controls [ 46 ]. Spermine was shown to inhibit the growth of PCa cells with low-metastatic potential but not those with high-metastatic potential, indicating its regulation effects depend on the metastatic state of PCa cells [ 47 ]. The exact link between the spermine concentration and PCa cell proliferation and metastasis needs further investigation.…”
Section: Discussionmentioning
confidence: 99%